Role of Video Assisted Thoracoscopic Surgery (VATS) in the Management of Pulmonary Sequestration; A Meta-Analysis - Kakamad, Fahmi H.; Amin, Bnar J. Hama; Ahmed, Harem K.; Najmadden, Zana B.; Tahir, Soran H.; Abdullah, Ari M.; Kareem, Pavel M.; Ahmed, Hawar S.; Mohammed, Shvan H.; Mohammed, Karukh K.; Abdalla, Berun A.; Abdalla, Sarhang Sedeeq; et al. (Current Respiratory Medicine Reviews, 2025)
BackgroundPulmonary sequestration is a rare birth defect. It is a nonfunctioning dysplastic lung tissue without connection to the tracheobronchial tree, and its blood supply is from one or more aberrant systemic arteries. The aim of this study is to review the current literature regarding the role of video-assisted thoracic surgery (VATS) in the management of pulmonary sequestration.ObjectiveThis review aims to assess the safety, efficacy, and outcomes of Video-Assisted Thoracoscopic Surgery (VATS) in managing pulmonary sequestration while considering patient characteristics, symptoms, arterial sources, surgical techniques, and postoperative advantages.MethodsThe Web of Science, PubMed, MEDLINE, and Google Scholar were searched for articles published in English. Article titles containing the words “Video-Assisted Thoracoscopic Surgery for Pulmonary Sequestration and/or VATS” were filtered out of the search to exclude a large portion of irrelevant studies. The extracted data were analyzed. The data extracted were presented as frequencies and percentages.ResultsAfter excluding the unrelated articles, 27 studies were identified for analysis; most of the studies (18) were case reports, with nine being case series, and the total number of patients who underwent pulmonary sequestration by VATS was 240. Both genders were equally affected (125, 52% were male and 115, 48% were female), the most common presenting symptom was coughing,and the descending thoracic aorta was the most common artery from which the feeders originated. About 149 patients (62.08%) underwent a lobectomy.ConclusionPulmonary sequestration can safely be treated by VATS at single or multiple ports with a shorter hospital stay, less postoperative pain, and fewer analgesic requirements.
Keywords: birth defect